Vloga shem certificiranja na področju trajnostnosti - Slak Piskar, Urban (Pravni letopis, 2025)
Sustainability certification schemes play an important role in reducing transaction costs, strengthening market confidence, and enabling consumers to make informed decisions. However, their effectiveness depends on the criteria for obtaining certification and the credibility and independence of the institutions that award the certificates. Over the past decade, irregularities and scandals have undermined confidence in certification labels, leading to increased legislative activity by the European Union. The main challenge is greenwashing, where suppliers provide consumers with false or misleading information about the sustainability of their products or themselves. New legislation, in particular Directive (EU) 2024/825 on empowering consumers for the green transition and the Proposal for a Directive on green claims, seeks to regulate the area with dual regulation of sustainability and environmental certification schemes. The directives set stricter conditions for the design, implementation, and monitoring of schemes and place a greater burden on providers to substantiate environmental claims. Nevertheless, questions remain regarding the division of competences and criteria for the classification of labels, as well as challenges in ensuring transparency and preventing eco-opportunism.
Keywords: certification schemes; consumer protection; environmental claims; environmental labels; greenwashing; informacijska asimetrija; information asymmetry; nelojalna konkurenca; okoljske trditve; okoljski znaki; sheme certificiranja; sustainability; Trajnostni razvoj; trajnostnost; transparency; transparentnost; unfair competition; Varstvo okolja; Varstvo potrošnikov; zeleno zavajanje